A study of socio-economic characteristics of the urbanities and their travel pattern in Nigeria - Samuel Babatunde Adedotun; Nurain Bola Tanimowwo; Rafiu Babatunde Ibrahim (Economic and Environmental Studies (E&ES), 2017)
This study, examined the relationship between socio-economic characteristics of the urbanities and their intra-urban mobility patterns in and across six selected cities in Osun State, Nigeria. Primary source of data for this work is the households across the cities studied. Instruments of data collection were focusing group discussion and questionnaire administered on the urban residents to investigate the socio-economic characteristics of the households and their travel patterns. Stratified sampling technique was employed to select two cities each from large, medium and small urban centres in Osun State. One percent (2133) of the households in the selected cities was systematically and randomly sampled for data collection. The resulting data were descriptively and inferentially analyzed using tables, percentages and multiple regression analysis. Analysis reveals a positive relationship between the socio-economic and travel pattern of urbanites in the cities. The study shows that about 92.5% of the variability in the observed travel pattern is explained by the socio-economic characteristics of urban residents. The study concluded with the suggestion that urban planning must be done in such a way that it will enhance effective travel pattern within and among different socio-economic groups.
Keywords: O18; R4; 330; Socio-economic characteristics; urbanites; travel pattern; Osun State